2016
DOI: 10.1186/s13033-016-0055-9
|View full text |Cite
|
Sign up to set email alerts
|

Barefoot therapists: barriers and facilitators to delivering maternal mental health care through peer volunteers in Pakistan: a qualitative study

Abstract: BackgroundPerinatal depression is a public health problem in low and middle income countries. Although effective psychosocial interventions exist, a major limitation to their scale up is the scarcity of mental health professionals. The aim of this study was to explore the facilitators and barriers to the acceptability of peer volunteers (PVs)—volunteer lay women from the community with shared socio-demographic and life experiences with the target population—as delivery agents of a psychosocial intervention for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(129 citation statements)
references
References 56 publications
5
124
0
Order By: Relevance
“…Perinatal anxiety is a critical public health priority, given the high prevalence, its tendency to predispose women to subsequent postpartum depression, and the negative impacts on child development and health outcomes. Lack of trained mental health specialists to deliver psychosocial interventions is a major barrier to addressing this problem (45). This simple intervention can be delivered by non-specialists under supervision and thus, if shown to be effective in subsequent large scale evaluations, could address the treatment gap for common mental disorders in LMICs (46).…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal anxiety is a critical public health priority, given the high prevalence, its tendency to predispose women to subsequent postpartum depression, and the negative impacts on child development and health outcomes. Lack of trained mental health specialists to deliver psychosocial interventions is a major barrier to addressing this problem (45). This simple intervention can be delivered by non-specialists under supervision and thus, if shown to be effective in subsequent large scale evaluations, could address the treatment gap for common mental disorders in LMICs (46).…”
Section: Discussionmentioning
confidence: 99%
“…This guide began by presenting PND symptoms and asking if they had seen someone with these symptoms and how they would describe them, then presented vignettes, or short stories with hypothetical characters, and closed by asking women about their personal experiences with depression. Vignettes were used due to the sensitivity of the study topic (18). The vignette in the interview guide centered around a woman with a new child experiencing signs of PND and receiving an HIV diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Padmanathan and De Silva [15] found that health service needs of the community and satisfaction with services contribute to acceptability of task-sharing in mental health care. Studies carried out in several countries have found that acceptability of task-sharing in mental health care is supported by perceptions of benefits such as accessibility, saving of time and money, and less stigma [16,17].…”
Section: Acceptabilitymentioning
confidence: 99%
“…Personal attributes of CHWs, such as gender, educational background, experience and knowledge, together with personal qualities (personality, being polite and friendly) also contribute to acceptability [15,17]. Proximity of non-specialist health workers to service users, and community endorsement of their role, support community acceptability [17], whereas level of training, support and supervision are significant factors affecting acceptability among professionals [16]. From a health system perspective, acceptability is influenced by the availability of appropriate infrastructure, workload, and issues such as assurance of confidentiality [15].…”
Section: Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation